Cultivar responses to water stress in potato effects of shoot and roots - Jefferies, R A (The New phytologist, 1993)
Two experiments using self- and reciprocal grafts, examined interaction between shoot and root in determining the response of potato (Solanum tuberosum L.) to water stress. Single-stemmed plants of the cultivars Cara and Desiree were grown in 15m pipes containing compost. Ten days after emergence, plants were either self- or reciprocally grafted. After the grafts had established, plants were either fully irrigated or subjected to drought treatments. Canopy expansion and leaf conductance were measured at regular intervals from the time that drought treatments were imposed. The production of shoot, root and tubers, and the distribution of root down the soil column were examined at the end of the experiments. Scions had a dominant effect in determining the partitioning of dry matter between shoot, root and tubers, with those of the cultivar Cara having larger shoots and roots and less partitioned into tubers. The influence of root stock and, by inference, tuber type was less significant. In both irrigated and draughted treatments leaf conductance was determined predominantly by the scion, with scions of Desiree having significantly greater leaf conductance than those of Cara. On only six occasions did the root stock have a significant effect. On these occasions leaf conductance was greater in plants with Desiree root stocks than in those with Cara root stocks. Drought reduced both dry matter production and the proportion of dry matter partitioned into tubers, and increased the proportion of dry matter in shoots and roots. Drought also increased the root: shoot ratio indicating that root growth was maintained to a greater extent than shoot growth. Specific root length (root length: weight ratio) was increased by drought in one experiment but not in the other. Differences among grafts in response to drought were determined largely by the scion, and only to a lesser extent by root stock, with scions or root stocks of Cara showing a greater shift in partitioning in favour of tubers to shoots and roots than those of Desiree